Prevalence and correlates of chronic diseases in an elderly population: A community-based survey in Haikou - Zhao, Chanjuan; Wong, Li Ping; Zhu, Qing; Yang, Hao (Public Library of Science, 2018)
Background The escalating problem of multiple chronic conditions among older adults in China draws public health attention due to increasing proportion of the elderly population. This study sought to assess the prevalence of and factors associated with four chronic diseases in older adults in Haikou, the capital city of Hainan Province, China. Method In this cross-sectional study, 9432 community-dwelling elderly people aged 60 years and older living in rural or urban areas in Haikou were investigated. The interviews collected selfreported information on the presence of four major chronic diseases, as well as socio-demographic characteristics, lifestyle factors and self-reported height and weight. Findings Overall, 31.7% (2961/9344) reported at least one of the four chronic diseases. The prevalence of hypertension, diabetes mellitus, COPD, and stroke was 26.0% (2449/9407), 8.0% (749/9371), 1.0% (95/9360), and 1.9% (175/9382), respectively. Common correlates of the four major chronic diseases were older age, being engaged in intellectual work, currently being a smoker and obesity. Gender, locality of residence, and alcohol consumptions were also found to be associated to some of the chronic conditions. Conclusion This finding indicates that multiple chronic conditions among elderly people in Haikou are prevalent and warrant special attention to reduce diseases burden and align health care services to cater the holistic elderly patients' need. © 2018 Zhao et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.